(3GdHQjbI GdeMehOjI aj TQM GdWQjbI GdeMeOjIs - (3GdMSjfj, GdNGOej, GdfbTHfOj, GdMfaj, CHh SYjO, eMeO Hf eUWai Hf YKeGf, J (B1176 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYdfG NjQ Cee (B((3cPG(B) (3CeI eQMheI eZahQI eKGHI ZGjI GdcQeKe deG cGf (B((3cPG(B) (3GdWQjbI GdeMeOjI cGadG deYXe gPg cdgG ObgG hLdgG de jged ObjbI ef GdegdcGJ hbWQI ef GdefLjGJGLJgOJ aj TQMg hJHjGfgeY RjGOGJ LdjdI hJhVjMGJ LejdIacCfeG MQjI HCf JSei HHQjbI (B((3cPG(B) (3eMehOjI aj TQM GdWQjbI GdeMeOjIs
(3BNQgG (B:s
(3GdeQGO ef GdChd Ydi fgL GdJCcjO dRjGOI GgJeGe HTCf GdMeO dbhI YXeI GdfYe GdJj efgG GdJUfja GdPj gh CLd GdYHGOGJ GdeJYOjI hCYXe GdCYeGd GdOGFeIs
(3fSNI efbhdI ef fSNI GdeDda aj (B26 (3QeVGf SfI (B1168(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 68s
(3eYLe GdeDdajf(B: 3 / 721s
(3cTa GdXfhf(B: 2 / 1113s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs